Nguyen van binh book street: redrawing urban public space in Ho Chi Minh City - Duy Thinh Do (Journal of Asian Architecture and Building Engineering, 2025)
Nguyen Van Binh Book Street exemplifies a new typology of urban public space in Vietnam, blending traditional streetscapes with cafés, green pockets, and pedestrian zones. While open spaces have been widely studied, adaptive and multifunctional models like this remain underexplored. Vietnam’s urban planning framework, heavily influenced by Western paradigms, often neglects localized social and spatial dynamics. Although Nguyen Van Binh is frequently celebrated and replicated, its adaptability across different urban contexts has not been rigorously assessed. Drawing from research findings, this study introduces the concept of Intersecting Public Space, a model defined by the convergence of commercial, cultural, recreational, and social functions within a fluid, unbounded environment. Nguyen Van Binh serves as a living example of this typology. Using Environmental Behavior Studies and a mixed-methods approach, the study investigates the relationship between spatial configuration and user behavior. Five categories of activity were identified, with sightseeing being the most common. However, several issues remain, including limited parking, inadequate public amenities, poor signage, and insufficient shelter from weather. To support the sustainable growth of book streets, improvements in spatial design, thematic programming, and accessibility are essential. Amid rising digital engagement, Intersecting Public Spaces offer a vital framework for sustaining inclusive and resilient urban life in Vietnam.